Kenyan MSM: no longer a hidden population. - Sanders, E; Jaffe, H; Musyoki, H; Muraguri, N; Graham, S (Lippincott, Williams and Wilkins, 2015)
In 2005, almost 25 years after the emergence of the HIV pandemic among MSM in the United States, the first substantial report of HIV and sexually transmitted infections (STIs) among a large group of MSM from Senegal was published in AIDS[1]. Although MSM received late recognition in the African HIV epidemic [2,3][2,3], Kenya was at the forefront in recognizing the vulnerabilities of this highly stigmatized population that feared legal authorities and had virtually no access to health services [4]. Numerous studies have since documented the elevated HIV/STI infection risks of African MSM, and donor responses have begun to focus on inclusion of MSM and their emerging organizations in HIV prevention and care programming in Africa [5]. Despite legal challenges and largely negative public debates [6], the Kenyan Ministry of Health and National AIDS and STI Control Programme has recognized that MSM are one of the key populations in need of urgent attention and have demonstrated their willingness to work with them [7].